Application of Hybrid Intelligent Algorithms in Path Planning. (March 2020) - Cuan, Ying; Li, Yike; Li, Xiangjuan
Abstract: Combining with the classical combinatorial optimization problem in the field of mathematics, this paper decides to take the optimal path planning problem as the research object. A new neighborhood search operator is introduced into the basic worker bee colony algorithm, and the optimization strategy of the algorithm is updated by combining the simulated annealing algorithm. Finally, the improved algorithm is applied to the optimal layout of the path planning, and the optimization results are compared with those of other algorithms. The simulation test shows that the intelligent optimization scheme proposed in this paper can get better optimization results, and has certain feasibility in the path planning. It provides valuable reference for solving the classical problems of the same type.